Flood Vulnerability Assessment of Kali Welang Floodplain by Using AHP-Based Methods - Ageng Dwi Wicaksono; Entin Hidayah; Retno Utami Agung Wiyono (U Karst, 2021)
Floods occur almost every year in a number of areas in the floodplain of Kali Welang. The floods have caused loss of materials and lives. Assessment of the vulnerability is essential for policy making in non-structural treatment of floods.  The objective of this paper is to compute and elaborate the flood vulnerability index in local scale to assess conditions that affect the magnitude of flood hazards.  This study identifies and evaluates the Flood Vulnerability Index (FVI) of an area by considering the factors of area’s exposure to floods, flood susceptibility, and flood resilience. The Analytic Hierarchy Process (AHP) is used to formulate the weights of each component. The values of the components were collected from interviews with policy makers from relevant governmental agencies. The inputs for the AHP were collected from the respondents in a questionnaire survey. This study selected 18 relevant indicators. The FVI results show very high vulnerability in local scale in one village and high vulnerability in other six villages. The results of this study can be used to construct non-structural strategies in flood mitigation by enhancing community’s resilience toward the flood. In addition, the results can be used for policy making process in spatial urban planning.